Charting a path between firm‐specific incentives and human capital‐based competitive advantage - Kryscynski, David; Coff, Russ; Campbell, Benjamin (Strategic Management Journal, 2021)
Research Summary Scholars have long recognized the theoretical and practical implications of firm‐specific human capital . However, we highlight that firm‐specific incentives (i.e., worker incentives that provide more utility to workers in the focal firm than similar incentives available at other employers) provide an important pathway to competitive advantages that has not been comprehensively examined in the extant organizational research. We address this gap by (a) defining firm‐specific incentives and showing why they are different from incentive conceptualizations and typologies in the extant literature, (b) articulating potential origins of firm‐specific incentives, and (c) formally proposing the conditions under which firm‐specific incentives facilitate human capital‐based competitive advantages. In so doing, we develop a cohesive theoretical framework of incentive‐based competitive advantage that integrates across multiple literatures. Managerial Summary Just as companies differentiate their products by creating unique value for customers, they also create unique value for their employees. Some companies do this by offering employee incentives, perks, and benefits that are highly unique to the company and difficult for other companies to imitate. These unique incentives, perks, and benefits can help these companies to attract, motivate, and retain top talent at a financial discount and, accordingly, can help these companies realize competitive advantages over their rivals.